2006
DOI: 10.1016/j.ejcts.2005.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The evidence on the effectiveness of management for malignant pleural effusion: a systematic review

Abstract: The aim of this study was to review systematically the available evidence on pleurodesis for malignant effusion, focusing on the choice of the agents, route of delivery and other strategies to improve outcomes. Four electronic databases (MEDLINE, EMBASE, Web of Science and Cochrane Controlled Trials Register) were searched, reference lists checked and letters requesting details of unpublished trials and data sent to authors of previous trials. Studies of malignant pleural effusion in humans were selected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
1
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(140 citation statements)
references
References 64 publications
4
119
1
13
Order By: Relevance
“…Talc has been reported as safe and efficacious for pleurodesis [15][16][17][18][19][20][21][22][23]. A Cochrane review reported that pleurodesis with talc provided the highest relative chance of MPE nonrecurrence when compared with bleomycin, tetracycline, mustine or chest-tube drainage alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…Talc has been reported as safe and efficacious for pleurodesis [15][16][17][18][19][20][21][22][23]. A Cochrane review reported that pleurodesis with talc provided the highest relative chance of MPE nonrecurrence when compared with bleomycin, tetracycline, mustine or chest-tube drainage alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Talc is widely recognized as the sclerosant agent of choice in view of its clinical effi cacy, safety profi le, and low cost, whereas thoracoscopic talc pleurodesis has been suggested as the most effective pleurodesis technique. 2,3,5 In fact, during video-assisted thoracoscopy, pleural fl uid can be removed completely, loculations and adhesions can be divided when present, and talc can be insuffl ated equally in the pleural space under visual control.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews 2,3 found that the relative risk for successful pleurodesis favored talc over other sclerosants and suggested that thoracoscopic talc poudrage was the technique of choice for pleurodesis in patients with MPE.…”
Section: Introductionmentioning
confidence: 99%
“…1A) T a b l e 1 . L a b o r a t o r y Da t a b e f o r e a n d a f t e r P l e u r o d e s i s wi t (5,6,8), talc (7,8), and so on. Although the success rates of pleurodesis using OK-432 and talc are 88% (5) and over 90% (8) …”
Section: F I G U R E 2 Ch E S T R a D I O G R A P H O N R E -A D Mimentioning
confidence: 99%